Identification, Functional Characterization, and Evolution of Terpene Synthases from a Basal Dicot. Issue 3 (8th July 2015) - Yahyaa, Mosaab; Matsuba, Yuki; Brandt, Wolfgang; Doron-Faigenboim, Adi; Bar, Einat; McClain, Alan; Davidovich-Rikanati, Rachel; Lewinsohn, Efraim; Pichersky, Eran; Ibdah, Mwafaq
Abstract : Sesquiterpene synthases for 1, 8-cineole, cadinene, and geranyllinalool appear early in angiosperm lineage. Abstract: Bay laurel ( Laurus nobilis ) is an agriculturally and economically important dioecious tree in the basal dicot family Lauraceae used in food and drugs and in the cosmetics industry. Bay leaves, with their abundant monoterpenes and sesquiterpenes, are used to impart flavor and aroma to food, and have also drawn attention in recent years because of their potential pharmaceutical applications. To identify terpene synthases (TPSs) involved in the production of these volatile terpenes, we performed RNA sequencing to profile the transcriptome of L. nobilis leaves. Bioinformatic analysis led to the identification of eight TPS complementary DNAs. We characterized the enzymes encoded by three of these complementary DNAs: a monoterpene synthase that belongs to the TPS-b clade catalyzes the formation of mostly 1, 8-cineole; a sesquiterpene synthase belonging to the TPS-a clade catalyzes the formation of mainly cadinenes; and a diterpene synthase of the TPS-e/f clade catalyzes the formation of geranyllinalool. Comparison of the sequences of these three TPSs indicated that the TPS-a and TPS-b clades of the TPS gene family evolved early in the evolution of the angiosperm lineage, and that geranyllinalool synthase activity is the likely ancestral function in angiosperms of genes belonging to an ancient TPS-e/f subclade that diverged from the kaurene synthase gene lineages before the split of angiosperms and gymnosperms.